Recent Advances in Antiemetics: New Formulations of 5-HT3 Receptor Antagonists in Adults. Issue 4 (July 2020) - Smith, Carrie; Smith, Michele; Cunningham, Regina; Davis, Susan
Abstract : Background: Despite the availability of effective antiemetic regimens, patients still experience chemotherapy-induced nausea and vomiting (CINV). 5-Hydroxytryptamine 3 (5-HT3 ) receptor antagonists (RAs) are the mainstay of CINV prevention, and updated antiemetic guidelines include new options. Objective: The aim of this study was to highlight advances in CINV management, focusing on new 5-HT3 RA formulations in adults, updated antiemetic guidelines, and the role of nurses. Methods: MEDLINE searches were conducted for English-language publications for the past 15 years using relevant search terms ("serotonin receptor antagonist, " "5-HT3 receptor antagonist, " "antiemetic, " "chemotherapy-induced nausea and vomiting") in the abstract or title. Abstracts at relevant major congresses for the past 3 years and additional pivotal publications were included. The most informative, relevant, and current publications were included. Results: 5-Hydroxytryptamine 3 RAs are effective in preventing acute (0–24 hours) CINV but less effective in the delayed phase (24–120 hours) given their short half-lives. Updated antiemetic guidelines include fixed-dose intravenous fosnetupitant and palonosetron (IV NEPA) and granisetron extended-release subcutaneous injection, a recently approved 5-HT3 RA formulation providing slow, controlled release of therapeutic granisetron concentrations for 5 days or longer. Nurses play a pivotal role in implementing updated guideline-recommended antiemetic regimens for highly and some moderately emetogenic chemotherapy regimens, comprising a 4- or 3-drug regimen of 5-HT3 RA, neurokinin-1 RA, and dexamethasone, with/without olanzapine. Conclusion: Newer antiemetic combinations and formulations provide flexibility for CINV prevention. Granisetron extended-release subcutaneous injection is a convenient subcutaneous granisetron option. Implications for Practice: Nurses play a critical role in understanding and using new antiemetic formulations and updated antiemetic guidelines in their practices.